Apakah ketimpangan menyebabkan inflasi? Tinjauan ekonomi politik inflasi, perpajakan dan utang pemerintah - Roel M. W. J. Beetsma; Frederick Frederick (Economic Journal of Emerging Markets, 2000)
A democratic society in which the distribution of wealth is unequal elects political parties that are likely to represent the interest of poor people. It is in the interest of clientele of the resulting governments to attempt to levy inflation taxes in order to erode the real value of debt service and redistributive from the rich to poor.